Photocatalytic discoloration of aqueous Malachite Green solutions by UV-illuminated TiO2 nano-particles under air and nitrogen atmospheres: Effects of counter-ions and pH - Rengifo Herrera, Julian Andres (2011)
Under air atmosphere, the photocatalytic discoloration of malachite green (MG) aqueous solutions (atriphenylmethane dye) in the presence of TiO2 and UV light followed an oxidative pathway, involving an N-demethylation process evidenced by a blue shifting of the main absorption band with a maximum at 618 nm. This oxidative process was affected by the nature of the dye counter-ion and the pH of the solution. At pH 6.0, the oxidation was found to be faster than at pH 3.0, perhaps due to the poor interactions between MG and the semiconductor surface. Furthermore, with the presence of oxalate as counter-ion, the oxidative photocatalytic discoloration was negatively affected mainly at acidic pH. Under nitrogen atmosphere, some evidence was found about the double behaviour of MG when involved in the photocatalytic discoloration reactions pertaining to TiO2 under these conditions. MG could be simultaneously oxidized, forming N-demethlyated by-products, or reduced, thus leading to leuco-malachite green (LMG) (a colorless and toxic substance) as the main product. The LMG formation is favoured at low pH in the presence of oxalate as counter-ion.